Coordinated RNA-Seq and peptidomics identify neuropeptides and G-protein coupled receptors (GPCRs) in the large pine weevil Hylobius abietis, a major forestry pest. (October 2018) - Pandit, Aniruddha A.; Ragionieri, Lapo; Marley, Richard; Yeoh, Joseph G.C.; Inward, Daegan J.G.; Davies, Shireen-Anne; Predel, Reinhard; Dow, Julian A.T.
Abstract: Hylobius abietis (Linnaeus), or large pine weevil (Coleoptera, Curculionidae), is a pest of European coniferous forests. In order to gain understanding of the functional physiology of this species, we have assembled a de novo transcriptome of H. abietis, from sequence data obtained by Next Generation Sequencing. In particular, we have identified genes encoding neuropeptides, peptide hormones and their putative G-protein coupled receptors (GPCRs) to gain insights into neuropeptide-modulated processes. The transcriptome was assembled de novo from pooled paired-end, sequence reads obtained from RNA from whole adults, gut and central nervous system tissue samples. Data analysis was performed on the transcripts obtained from the assembly including, annotation, gene ontology and functional assignment as well as transcriptome completeness assessment and KEGG pathway analysis. Pipelines were created using Bioinformatics tools and techniques for prediction and identification of neuropeptides and neuropeptide receptors. Peptidomic analysis was also carried out using a combination of MALDI-TOF as well as Q-Exactive Orbitrap mass spectrometry to confirm the identified neuropeptide. 41 putative neuropeptide families were identified in H. abietis, including Adipokinetic hormone (AKH), CAPA and DH31. Neuropeptide F, which has not been yet identified in the model beetle T. castaneum, was identified. Additionally, 24 putative neuropeptide and 9 leucine-rich repeat containing G protein coupled receptor-encoding transcripts were determined using both alignment as well as non-alignment methods. This information, submitted to the NCBI sequence read archive repository (SRA accession: SRP133355), can now be used to inform understanding of neuropeptide-modulated physiology and behaviour in H. abietis ; and to develop specific neuropeptide-based tools for H. abietis control. Graphical abstract: Highlights: The transcriptome of the economically important insect pest, the large pine weevil, was assembled de novo from RNA-Seq data. Integrated approach using transcriptomics and peptidomics performed to identify neuropeptides and respective receptors. 41 putative neuropeptide precursor sequences, 24 putative neuropeptide and 9 putative LGR receptor sequences identified. The raw sequence reads from the gut, CNS and whole body tissues have been submitted to the NCBI SRA database.